Computer attitude, computer anxiety and computer self-efficacy :a study among preservice and inservice teachers in UNIMAS - Wong, King Chard (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study aims to investigate the current profile of computer attitude, computer anxiety and computer Self-efficacy among preservice and inservice teachers of UNIMAS. The objectives of the study are to investigate the computer experience and usage of undergraduates who study education programmes, while establishing a connection between computer attitude, computer anxiety and computer self-efficacy with other variables. 164 undergraduates participated in this study and the data were collected through questionnaire. The survey result showed that the all the respondents were equipped with a personal computer and internet connection was available to most to them. The respondents also use the computer for hours and most of them have at less 5 years of computer experience. The survey showed that the respondents have high computer attitude, moderate computer anxiety and high computer self-efficacy. A strong relationship was also found between computer attitude, computer anxiety and computer self-efficacy. Not only that, computer attitude and computer self-efficacy were found to be strongly related with internet connection and computer experience. Computer anxiety was found to be negatively related with internet connection, computer experience and computer usage.